2009
DOI: 10.1021/jp900349g
|View full text |Cite
|
Sign up to set email alerts
|

Boron-Doped Palladium Nanoparticles on Carbon Black as a Superior Catalyst for Formic Acid Electro-oxidation

Abstract: Highly dispersed boron-doped palladium nanoparticles supported on carbon black (Pd-B/C) with high Pd loading (ca. 40 wt % Pd) are synthesized through an aqueous process using dimethylamine borane as the reducing agent. The as-prepared Pd-B/C catalyst shows extraordinary activity toward formic acid electrooxidation compared to that of a commercially available Pd/C catalyst and the one prepared by using NaBH 4 as the reductant. Subsequent thermal treatment further enhances the durability of the electro-oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(121 citation statements)
references
References 48 publications
4
116
0
1
Order By: Relevance
“…4). The ECSA was estimated by integrating the voltammograms corresponding to the CO-stripping peak by assuming a charge of 420 mC cm À2 for electro-oxidation of the CO monolayer on the catalyst surfaces [19]. It found that the ECSA value of Pd/SnO 2 eS (79.5 m 2 g À1 ) was larger than those of Pd/SnO 2 eP (35.6 m 2 g À1 ) and Pd/XC-72 (69.3 m 2 g À1 ), indicating that more active sites are available at the Pd/SnO 2 eS catalyst [20].…”
Section: Resultsmentioning
confidence: 99%
“…4). The ECSA was estimated by integrating the voltammograms corresponding to the CO-stripping peak by assuming a charge of 420 mC cm À2 for electro-oxidation of the CO monolayer on the catalyst surfaces [19]. It found that the ECSA value of Pd/SnO 2 eS (79.5 m 2 g À1 ) was larger than those of Pd/SnO 2 eP (35.6 m 2 g À1 ) and Pd/XC-72 (69.3 m 2 g À1 ), indicating that more active sites are available at the Pd/SnO 2 eS catalyst [20].…”
Section: Resultsmentioning
confidence: 99%
“…The above XRD measurement has proved the dilation of the lattice constant of Pd nanoparticles in Pd/TiO 2 (ADR) and Pd/TiO 2 (R). Therefore, the dilated lattice constant of Pd-Pd is beneficial to the absorption/desorption of hydrogen in the bulk Pd compared to the compressed one [39]. Interestingly, it has been reported that a dilated Pd lattice showed higher activity than that of a compressed lattice for formic acid electrooxidation [40].…”
Section: Resultsmentioning
confidence: 99%
“…The addition of Pb to Pd stabilized it significantly to deactivation during formic acid oxidation. Wang et al [65] synthesized highly dispersed boron-doped Pd nanoparticles supported on carbon black with high Pd loadings (ca. 40 wt.…”
Section: (3) Other Alloysmentioning
confidence: 99%